The Influence of Profitability, Liquidity, and Leverage on Firm Value in Manufacturing Companies on the Indonesia Stock Exchange - Tanya Tata Putri Srikandi; Hwihanus (Takaza Innovatix Labs Ltd., 2026)
This study aims to explore the impact of probability, liquidity, and leverage on the valuation of companies listed on the Indonesia Stock Exchange (IDX). Company valuation is a crucial indicator for investors to assess the performance and future prospects of a company, therefore, analysis of fundamental factors such as profitability, liquidity, and leverage must be conducted empirically. The approach used in this study is quantitative by utilizing secondary data obtained from the annual financial reports of manufacturing companies listed on the IDX for a certain period. Profitability is measured by Return on Assets (ROA), liquidity is measured by the Current Ratio (CR), Leverage is assessed by the Debt to Equity Ratio (DER), and company valuation is evaluated using Price to Book Values ​​(PBV). The sampling method was carried out using purposive sampling according to predetermined criteria, and data analysis was conducted using multiple linear regression with panel data. The findings of this study are expected to be able to show that profitability, liquidity, and leverage contribute to company valuation, both individually and simultaneously. The results of this study are expected to provide theoretical contributions to the development of literature in financial management, as well as practical contributions to the management of corporate financial structures and for investors in the investment decision-making process in manufacturing companies in Indonesia